Evaluation of antifungal activity of some oils from Algerian medicinal plants against Aspergillus flavus strain produced aflatoxins - A. Amrouche, H. Benmehdi, A. Moussaoui, K. Mebarki, A Chaoufi, A. Saneba, A. Lazouni .H, D. Chabane Sari (Journal of Applied Pharmaceutical Science)
Antifungal activity of the oils extracts of Citrullus colocynthis L., Linum usitatissimum L., Nigella sativa L. collected from Bechar Department in the region of (Algeria) has been evaluated in this present study. Two methods were used in this investigation: radial growth on solid medium and biomass on liquid medium. The oils extracts were obtained by Soxhlet extraction of the seeds part. The values of physicochemical indices of our oils such as acid, acidity and peroxide were also determined. The results of the antifungal potency revealed that the seeds oils exhibited different degrees of inhibition against Aspergillus flavus MTTC 2799. However, evaluation of radial growth on Potatoes Dextrose Agar (PDA) solid medium showed slight mycelial growth proportional to oil concentration added to the medium. Antifungal indices investigation allowed as to put our oils in the order of effectiveness: L. usitatissimum (29%) > C. colocynthis (26.5 %) > N. sativa (18.75 %). Evaluation of Aspergillus flavus biomass production on Potatoes Dextrose Broth (PDB) on liquid medium revealed that the studied oils produced a variable weight reduction (C. colocynthis and L. usitatissimum at concentration superior to (80µl/ml). On the contrary, N. sativa oil reduced Aspergillus flavus biomass at concentrations of 80µl/ml and 100µl/ml.
Keywords: Antifungul activity, oils, Citrullus colocynthis L., Linum usitatissimum L., Nigella sativa L., Aspergillus flavus